Transitivity Processes in Thunberg’s Viral Speech: A Systemic Functional Linguistics Study - Hesti Raisa Rahardi; Eva Tuckyta Sari Sujatna; Heriyanto (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study analyses the relationship between clause structures and social construction of the meaning found in verbal speeches. Drawing on Halliday's transitivity system particularly the processes element rooted in Systemic Functional Linguistics, the present study attempts to investigate the distribution of transitivity processes found in viral speech of Greta Thunberg at 2019 United Nation Climate Summit held in New York City. Moreover, through descriptive qualitative analysis, the study aims to reveal the function expressed by the processes found in the speech. To this end, it is found that only five out of six process types namely material, mental, relational, verbal, and behavioral processes found in the speech. Moreover, Thunberg used relational processes, mental processes, and material processes more than verbal processes and behavioral processes. The five processes further serve different functions in the speech. Yet, all of the processes occurred in the speech are generally used to deliver Thunberg’s critics over the world leader’s slow response in handling the climate issue. Besides, the processes also used to convince the audience and people in general to start doing something for the climate. The implication of this research is expected to give the information on how language structure is used by the environmental activist in her agenda to persuade people.